Early programming of reproductive health and fertility: novel neuroendocrine mechanisms and implications in reproductive medicine - Sánchez-Garrido Miguel Angel; García-Galiano David; Tena-Sempere Manuel (OXFORD UNIV PRESS, 2022)
BACKGROUND
According to the Developmental Origins of Health and Disease (DOHaD) hypothesis, environmental changes taking place during early maturational periods may alter normal development and predispose to the occurrence of diverse pathologies later in life. Indeed, adverse conditions during these critical developmental windows of high plasticity have been reported to alter the offspring developmental trajectory, causing permanent functional and structural perturbations that in the long term may enhance disease susceptibility. However, while solid evidence has documented that fluctuations in environmental factors, ranging from nutrient availability to chemicals, in early developmental stages (including the peri-conceptional period) have discernible programming effects that increase vulnerability to develop metabolic perturbations, the impact and eventual mechanisms involved, of such developmental alterations on the reproductive phenotype of offspring have received less attention.
OBJECTIVE AND RATIONALE
This review will summarize recent advances in basic and clinical research that support the concept of DOHaD in the context of the impact of nutritional and hormonal perturbations, occurring during the periconceptional, fetal and early postnatal stages, on different aspects of reproductive function in both sexes. Special emphasis will be given to the effects of early nutritional stress on the timing of puberty and adult gonadotropic function, and to address the underlying neuroendocrine pathways, with particular attention to involvement of the Kiss1 system in these reproductive perturbations. The implications of such phenomena in terms of reproductive medicine will also be considered.
SEARCH METHODS
A comprehensive MEDLINE search, using PubMed as main interface, of research articles and reviews, published mainly between 2006 and 2021, has been carried out. Search was implemented using multiple terms, focusing on clinical and preclinical data from DOHaD studies, addressing periconceptional, gestational and perinatal programming of reproduction. Selected studies addressing early programming of metabolic function have also been considered, when relevant.
OUTCOMES
A solid body of evidence, from clinical and preclinical studies, has documented the impact of nutritional and hormonal fluctuations during the periconceptional, prenatal and early postnatal periods on pubertal maturation, as well as adult gonadotropic function and fertility. Furthermore, exposure to environmental chemicals, such as bisphenol A, and maternal stress has been shown to negatively influence pubertal development and gonadotropic function in adulthood. The underlying neuroendocrine pathways and mechanisms involved have been also addressed, mainly by preclinical studies, which have identified an, as yet incomplete, array of molecular and neurohormonal effectors. These include, prominently, epigenetic regulatory mechanisms and the hypothalamic Kiss1 system, which likely contribute to the generation of reproductive alterations in conditions of early nutritional and/or metabolic stress. In addition to the Kiss1 system, other major hypothalamic regulators of GnRH neurosecretion, such as gamma-aminobutyric acid and glutamate, may be targets of developmental programming.
WIDER IMPLICATIONS
This review addresses an underdeveloped area of reproductive biology and medicine that may help to improve our understanding of human reproductive disorders and stresses the importance, and eventual pathogenic impact, of early determinants of puberty, adult reproductive function and fertility.